2001
DOI: 10.1007/bf01288362
|View full text |Cite
|
Sign up to set email alerts
|

Acclimative changes in root epidermal cell fate in response to Fe and P deficiency: a specific role for auxin?

Abstract: Root hair formation and the development of transfer cells in the rhizodermis was investigated in various existing auxin-related mutants of Arabidopsis thaliana and in the tomato mutant diageotropica. Wild-type Arabidopsis plants showed increased formation of root hairs when the seedlings were cultivated in Fe- or P-free medium. These extranumerary hairs were located in normal positions and in positions normally occupied by nonhair cells, e.g., over periclinal walls of underlying cortical cells. Defects in auxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Although application of IAA increases root hair length and density in plants grown on high Pi, it has little effects on root hairs in plants grown on low Pi (Bates and Lynch, 1996;Ma et al, 2001a). Furthermore, low Pi stimulated root hair elongation in the hairless auxin-resistant mutant axr1 and axr2, as well as in the auxin-insensitive mutant aux1, in a manner similar to wild type (Figure 9) (Ma et al, 2001a;Schikora and Schmidt 2001;Schmidt and Schikora, 2001). Thus, although auxin does affect root hair development, it appears that low Pi can increase root hair length and density in a manner that is at least partially independent of auxin.…”
Section: Morphology Of the Root Systemmentioning
confidence: 90%
“…Although application of IAA increases root hair length and density in plants grown on high Pi, it has little effects on root hairs in plants grown on low Pi (Bates and Lynch, 1996;Ma et al, 2001a). Furthermore, low Pi stimulated root hair elongation in the hairless auxin-resistant mutant axr1 and axr2, as well as in the auxin-insensitive mutant aux1, in a manner similar to wild type (Figure 9) (Ma et al, 2001a;Schikora and Schmidt 2001;Schmidt and Schikora, 2001). Thus, although auxin does affect root hair development, it appears that low Pi can increase root hair length and density in a manner that is at least partially independent of auxin.…”
Section: Morphology Of the Root Systemmentioning
confidence: 90%
“…Growth of Arabidopsis seedlings in Pi-limiting conditions causes an increase in the length and frequency of root hairs, thus enlarging the root surface area and enhancing the ability of the roots to absorb phosphorus (Schikora and Schmidt, 2001;Ma et al, 2003; Fig. 3A).…”
Section: Pi Starvation Enhancement Of Root Hair Elongation Is Ga Depementioning
confidence: 99%
“…Recently, it has been reported that the phytohormones ethylene and auxin are involved in Pi starvationinduced root hair development in Arabidopsis (Schikora and Schmidt, 2001;He et al, 2005). To investigate the possible role of the GA-DELLA system in Pi deficiencyinduced changes in the formation and growth of root hairs, we compared the roots of wild-type, gai-t6 rga-t2 rgl1-1 rgl2-1, ga1-3, and ga1-3 gai-t6 rga-t2 rgl1-1 rgl2-1 seedlings.…”
Section: Pi Starvation Enhancement Of Root Hair Elongation Is Ga Depementioning
confidence: 99%
“…A variety of signaling molecules and plant hormones modulate the Fe deficiency response in a positive manner, such as nitric oxide (Graziano et al, 2002;Graziano and Lamattina, 2007;Chen et al, 2010;García et al, 2010) and auxin (Schikora and Schmidt, 2001;Chen et al, 2010), or in a negative manner, like cytokinin (Sé gué la et al, 2008). Experiments with the plant hormone ethylene in different dicot plants indicated a physiological connection between ethylene and iron deficiency signaling.…”
Section: Introductionmentioning
confidence: 99%